A grounded-theorys study of meta-attention in golfers - Oliver, A.; McCarthy, P. J.; Burns, L. (The Sport Psychologist, 2020)
This study sought to construct a theoretical understanding of meta-attention in golfers. Eight male golfers (7 competitive-elite and 1 successful-elite) were interviewed about their experiences of attentional processes in competitive golf. A Straussian grounded-theory approach was used throughout the research process, and interview transcripts were analyzed using open, axial, and selective coding. Results indicated that meta-attention is resource based, with metacognitive reflections of logistic and shot resources that facilitate attentional control. Attentional control required successful target selection, consistent preshot routines, and consistent postshot routines. Failures in wider or immediate resources or failure to initiate control routines can lead to internal distraction. The emergent theory provides an understanding of the function of meta-attention in golf performance that can be used by golfers, coaches, or psychologists to improve attentional strategies.